Assessment of Pattern, Determinants and Treatment Practices of Menstrual Disorders Among Medical Undergraduate Students - Joseph, Nitin; Alfiya, Ayisha; Khurana, Megha; Divya, Maheshwari; Gupta, Kritika; Thangavelu, Muthu R. R. (Current Women's Health Reviews, 2022)
Background: Menstruation-related symptoms (MRSs) have been observed to result in absenteeism from either work or education, more commonly among women below 21 years than women of any other age group. Despite its high prevalence and associated ill effects, it is generally ignored even by medical students. Objectives: This study was conducted to assess the pattern, determinants, and treatment practices of menstrual disorders among undergraduate medical students. Methods: This was a cross-sectional study conducted among 215 female medical students from first to final year. Data were collected by using a self-administered questionnaire. The height and weight of participants were measured using standard procedures. Results: The most common menstrual disorders reported by participants over the past six months were dysmenorrhoea (191(88.8%)) followed by irregular cycles (43(20.0%)). In multivariable analysis, the presence of polycystic ovarian syndrome (PCOS) and excessive consumption of coffee was associated with irregular menstrual cycles; the presence of anaemia was associated with menorrhagia, the presence of fibroids and age of participants were associated with polymenorrhoea, excessive chocolate consumption was related to intermenstrual bleeding, excessive chocolate consumption, presence of anaemia, and low body mass index (BMI) were associated with premenstrual syndrome. Self-medication was reported by 15 (42.9%) out of the 35 participants on treatment. Conclusion: Dysmenorrhoea and menstrual irregularities were common among participants. They need to limit potential risk factors like excessive consumption of coffee and chocolates. Additionally, screening for anaemia, PCOS, fibroids and low BMI needs to be done. Self-medication practices need to be also dissuaded in the setting.
Keywords: Menstrual disorders